Karakter Anatomi Daun sebagai Bentuk Adaptasi Tumbuhan Penyusun Zonasi Mangrove di Banggai Kepulauan, Provinsi Sulawesi Tengah - Eka Fatmawati Tihurua; Esthi Liani Agustiani; Kusuma Rahmawati (Universitas Diponegoro, 2020)
Mangrove is an essential ecosystem that are located in the transition area of fresh and sea water. Therefore, species that grow are typical species that are able to adapt to the saline environment. The aim of this research is to characterize leaf anatomical structure for every species that compose the communities found in each mangrove zonations, including their similarities and dissimilarities characteristic. Sampling of examined leaf was carried out in the mangrove areas of Peling Island and Bakalan Island by making plots in four sites of the mangrove ecosystem area. Methods for leaf anatomical preparations were carried out using the paraffin-tert-butanol and paradermal sections. Anatomical characters as an adaptation to saline habitat are found in all species of mangrove plants, including thick cuticle and epidermal cells, thick leaves and water-storage tissue (hypodermis). In addition, there is found the presence of cork warts and sclereid as characteristic of the genus Rhizophora. Based on quantitative character observations, the mesophyll (palisade to sponge) ratio range from 0.28 ± 0.04 μm to 1.19 ± 0.42 μm, leaf thickness ratio 289,41 ± 38,21 μm to 695,20 ± 97,50 μm and the highest stomata density is owned by Lumnitzera littorea